1982
DOI: 10.1002/1097-0142(19820115)49:2<388::aid-cncr2820490230>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid carcinoma: A clinical study of seven cases of functioning and two cases of nonfunctioning parathyroid cancer

Abstract: Seven cases of functioning and two cases of nonfunctioning parathyroid carcinoma are presented together with a general discussion of this disease. Functioning parathyroid carcinoma may be associated with prolonged survival. The morbidity and mortality from this disease are generally related to the prolonged hypercalcemia that occurs. The hypercalcemia is best treated with excision of local recurrences; however, this surgery is most often palliative and seldom curative. The best operative results were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
7

Year Published

1986
1986
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 32 publications
1
59
0
7
Order By: Relevance
“…Infact, she never had very high levels of hypercalcaemia suggesting the possibility of non functioning parathyroid carcinoma [10,11]. Nonproducing parathyroid carcinoma compares unfavourably with producing parathyroid carcinoma in terms of tumour progression and prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…Infact, she never had very high levels of hypercalcaemia suggesting the possibility of non functioning parathyroid carcinoma [10,11]. Nonproducing parathyroid carcinoma compares unfavourably with producing parathyroid carcinoma in terms of tumour progression and prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…8 Although repeated surgical interventions have proven beneficial in palliative care, 9 excision of progressive tumor is not consistently curative. 10 In a recent review of 10 cases of parathyroid carcinoma treated at the Princess Margaret Hospital, 11 it was suggested that local RT to the tumor bed may decrease the strong predilection for local progression of the disease.…”
mentioning
confidence: 99%
“…17 Death in patients with nonfunctional parathyroid tumors is primarily due to the volume of regional disease and metastases. 25 …”
Section: Discussionmentioning
confidence: 99%